Penerapan Manajemen Proyek Dalam Pembangunan Taman Kelurahan Adaptif di Kawasan Lahan Basah Kelurahan Alalak Selatan - Ananta, Angelica Sherren (Fakultas Teknik Universitas Hamzanwadi, 2025)
The development of neighborhood-scale parks plays an important role in providing community-based public facilities tailored to local environmental and social needs. In Alalak Selatan Subdistrict, Banjarmasin, the presence of wetland terrain and tidal conditions requires a site-specific approach in project planning and execution. This study analyzes the application of project management principles in the design and conceptualization of a community park in such challenging conditions. A qualitative case study method was used, utilizing Google Earth imagery for site analysis, AutoCAD for technical design, and SketchUp for 3D visualization. Project components such as the Work Breakdown Structure (WBS), estimated Budget Plan (RAB), scheduling, and quality control aspects were reviewed in line with standard project management practices. The results show that adaptive planning, cost estimation based on local material prices, and risk identification strategies contribute significantly to ensuring feasibility and functionality. This approach offers a practical reference for small-scale public facility projects in similar environmental contexts.